Microestructura CMOS para la Manipulación de Micropartículas - Fernández Morales, Flavio Humberto; Duarte, Julio Enrique; Samitier Martí, Josep (Ingeniería, 2004)
Artificial and natural microparticle manipulation is a common operation in biotechnology and medicine. As a consequence, there is an enormous interest in developing versatile and efficient devices to replace the traditional laboratory methods. Thus, electric fields have been used as an actuation mechanism because they only require a few electrodes to make particle manipulators. In fact, there are some applications which employ microsystem technologies to fabricate these manipulation tools. However, it could be interesting to have at disposal devices developed in standard microelectronics technology, in order to simplify their processing as well as to reduce their manufacturing costs. As a result, in this work it is outlined the design and fabrication of a microstructure in CMOS technology, in order to demonstrate the viability of microparticle manipulation through inhomogeneous electric fields. Furthermore, some experimental results with particles of 2 μm in diameter are shown.